What to do about African Honey Bees: A Consumer Guide - Michael K. O’Malley; James D. Ellis; Anita S. Neal (EDIS)
ENY-141, a 3-page fact sheet by M. K. O’Malley, J. D. Ellis, and A. S. Neal, provides information about Africanized honey bees (AHB), which have been labeled “killer” bees, steps people can take to avoid negative interactions, how to handle stings, and bee-proofing basics. Published by the UF Department of Entomology and Nematology, December 2007.